Students’ Speaking Ability Through Debate Technique at Second Semester Students of Development Economics Major at Stie-Sak Academic Year 2024/2025 - Yelnim, Yelnim (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study is based on the important of speaking skill. Speaking was important to be learnt because speaking is the way to communicate with other people in order to deliver opinion and express idea, but in fact the students’ ability in speaking English is low. It is caused by several factors such as there are some elements of speaking such as vocabulary, pronunciation, grammar and fluency that must be mastered by students in order to be good English speaker. In this research, the researcher used debate technique to improve students’ speaking ability. The main objective of this study is to describe the implementation of debate technique in teaching speaking and to identify how much students’ speaking ability improvement after being taught by using debate technique. This study is classroom action research that was done in two cycles. The data collection was done using observation and test. The data from the observation that had been taken from every cycle analyzed descriptively while the data from test were analyzed quantitatively. The implementation of debate technique in teaching speaking at second semester students of Development Economics at STIE-SAK academic year 2024/2025 was conducted in two cycles including cycle one and cycle two. The result of this study shows that using debate technique can improve students’ speaking ability. This is proven by students’ test score that improved in each cycles. The result of this study is helpful information for English lecturer in teaching speaking.